Evolution of ideas about the body in modern physical education - Vypasniak, Ihor; Fedyniak , Nazarii (Journal of Education, Health and Sport, 2022)
Relevance. The need to study the evolution of understanding the body and corporeality is extremely relevant. This relevance is due to the spread of practices in modern society that promote a developed and aesthetic body. These trends indicate the importance of studying corporeality not only from a biological but also a socio-cultural perspective. The status of corporeality as an object of scientific knowledge, which has a centuries-old history, is constantly changing under the influence of social development. Research tasks. Studying corporeality from a socio-cultural perspective. Research results. In the modern world, characterized by rapid technological development, information revolution and transformation of gender relations, the status of the body has undergone unprecedented changes. This significantly increases scientific interest in the phenomenon of corporeality and requires a revision of existing approaches to the study of human bodily existence as an integral characteristic. From the standpoint of such an integral approach, bo this function is not limited to understanding the body as a natural human being. It is interpreted as a complex phenomenon determined by cultural and historical conditions. This is expressed in specific forms of movement that acquire certain meanings and are lived by the human body itself. Modern trends in health demonstrate an increased connection between quality of life, physical condition and beauty. This connection is based on a paradigm that considers the body and spirit as a single whole. According to this concept, work on the body is considered a means of spiritual self-improvement. The health industry is moving from treatment to prevention, which is confirmed by the growing popularity of various types of health-improving motor activity. Conclusions. The paradigmatic approach to the study of the spatial organization of the body is an effective tool for scientific research, since it contributes to the development of theoretical foundations, humanization of practices and the introduction of health technologies. This paradigm is based on the following elements: the formation of a system of knowledge and skills necessary for diagnosing the state of the spatial organization of the body; awareness of the cultural influences that determine its formation; a deep understanding of the phenomenon and social significance of the spatial organizat ion of the body.